Attention Deficit Hyperactivity Disorder (ADHD) in Children Consuming Junk Food: LMRJ - Rawan, Bakht (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
The current study is aimed at determining relationship between junk food consumption and Attention Deficit Hyperactivity Disorder (ADHD) in school going children. Standard questionnaires for the diagnosis of ADHD, junk food consumption among children and their mothers during pregnancy and lactation were distributed among children and parents of enrolled students. Data retrieved was assessed for statistically significant associations.Parents of 84 students were contacted, of whom 47 were enrolled into the study. A total of 8 (17.02%) student were found to have ADHD, with a higher frequency in male students. Junk food consumption was found to have an association with ADHD. ADHD is a common finding in school going children of district Kohat. The frequency is particularly high in male children and is strongly associated junk food consumption.